Groves, Tamar y González-Pérez, Alicia (Eds.). Women and knowledge. From the challenges of the past to empowerment for the future - Soriano Moreno, Silvia (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2022)
Este artículo reseña: Groves, Tamar y González-Pérez, Alicia (Eds.). Women and knowledge. From the challenges of the past to empowerment for the future. Roma: Aracne, 2018. 138 pp. ISBN: 978-88-255-1084-3.